ANALYSIS OF SPACE USE AROUND THE MOSQUE AS AN ECONOMIC SPACE IN SYAIKHONA KHOLIL MOSQUE MADURA - Septia Heryanti; Oktavi Elok Hapsari (Vitruvian : Jurnal Arsitektur, Bangunan dan Lingkungan, 2023)
The mosque is a center of worship for Muslims. Besides a place to pray, researchhas shown that the role of the mosque is not merely in spiritual concern. Mosques also have the role ofeducation, social and economic development. However, the relationship between the role of the mosque and the space use is yet unknown. The activity that creates space use should be analyzed to see whether created space meets the needs or not. This research aims to explore the space use of Syaikhona Kholil mosques in Bangkalan Madura. It has a unique layout with the tomb of the Indonesian ulama inside. Thus, the mosque is always crowded as a pilgrimage destination. The existence of this religious activity eventually led to economic activity to support the needs of the pilgrims, both religious needs and daily needs. Based on a qualitative approach, the primary data was collected through field observation, mapping of economic activities surrounding the mosque, and interviews. The result of the research shows that the activity of social and economic determined thespace used at the Syaikhona Kholil mosque. The economic space that are supporting the enlivenment of the mosque is not only shophouses, kiosks, and paddlers but also a large parking area. The tomb of KH Syaikhona Kholil affects the development of economic activities in the vicinity, changes the space usedaround it, and improves the lives of communities.